Пьесы - Булгаков Михаил Афанасьевич; Булгаков Михаил Афанасьевич (1990)
Экземпляры: аб. (1991) / Инвентарный номер: 33258 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6